2014
DOI: 10.1002/2013ja019197
|View full text |Cite
|
Sign up to set email alerts
|

Storm time enhancements of 630.0 nm airglow associated with polar cap patches

Abstract: We examined the brightness of 630.0 nm airglow, I630, associated with polar cap patches observed during a magnetic storm that occurred on 22 January 2012. Brightness was measured using an all‐sky imager (ASI) located at Longyearbyen, Svalbard. The observed I630 was compared with the F region electron density observed by the European Incoherent Scatter Svalbard Radar (ESR). The I630 was positively correlated with the F2 layer peak electron density, NmF2, and inversely correlated with the altitude of the F2layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…These authors recently presented 630.0 nm airglow intensity variations over Svalbard associated with polar cap patches during 1800–2400 UT on 22 January 2012. Although not reported by Sakai et al [], ∼40 min periodicity can be noticed in the observed 630.0 nm airglow intensity variation during 1800–2030 UT on this night. Therefore, it is clear that the ∼40 min fluctuation in IEF y has a global effect on this particular night and strengthens the argument for the DP2 origin of the fluctuations with similar periodicity observed over the equatorial region during midnight hours.…”
Section: Discussioncontrasting
confidence: 63%
“…These authors recently presented 630.0 nm airglow intensity variations over Svalbard associated with polar cap patches during 1800–2400 UT on 22 January 2012. Although not reported by Sakai et al [], ∼40 min periodicity can be noticed in the observed 630.0 nm airglow intensity variation during 1800–2030 UT on this night. Therefore, it is clear that the ∼40 min fluctuation in IEF y has a global effect on this particular night and strengthens the argument for the DP2 origin of the fluctuations with similar periodicity observed over the equatorial region during midnight hours.…”
Section: Discussioncontrasting
confidence: 63%
“…Similarly, we map blue (427.8 nm) emission snapshots to 110 km. These are typical mapping altitudes at these wavelengths (Gulledge et al 1968;Axelsson et al 2014;Sakai et al 2014). However, there are some errors associated with this mapping.…”
Section: Data Set and Event Selectionmentioning
confidence: 80%
“…However, there are some errors associated with this mapping. To estimate the errors, we use intensity profiles for airglow red emission presented by Sakai et al (2014), which showed that the airglow emission of polar cap patches is peaked at ~280 km altitude during disturbed time. The errors from the 230 km altitude mapping can be estimated as:…”
Section: Data Set and Event Selectionmentioning
confidence: 99%
“…As shown in Taguchi et al (2012), the 630.0 nm (red) line data from this EMCCD camera can provide detailed information about the dynamic features of moving cusp auroral structures. The high sensitivity of this camera is also very effective for identifying the structure of polar cap patches (Hosokawa et al 2013a(Hosokawa et al , 2013bSakai et al 2014). Thus, in the current study, we used 630.0 nm wavelength images.…”
Section: Instrumentationmentioning
confidence: 99%